Domain isolation, expression, purification and proteolytic activity of the metalloprotease PrtV from Vibrio cholerae - Edwin, Aaron; Grundström, Christin; Wai, Sun N.; Öhman, Anders; Stier, Gunter; Sauer-Eriksson, A. Elisabeth (Protein expression and purification, 2014)
The metalloprotease PrtV from Vibrio cholerae serves an important function for the bacteria’s ability to invade the mammalian host cell. The protein belongs to the family of M6 proteases, with a characteristic zinc ion in the catalytic active site. PrtV constitutes a 918 amino acids (102kDa) multidomain pre-pro-protein that so far has only been expressed in V. cholerae. Structural studies require high amounts of soluble protein with high purity. Previous attempts for recombinant expression have been hampered by low expression and solubility of protein fragments. Here, we describe results from parallel cloning experiments in Escherichia coli where fusion tagged constructs of PrtV fragments were designed, and protein products tested for expression and solubility. Of more than 100 designed constructs, three produced protein products that expressed well. These include the N-terminal domain (residues 23-103), the PKD1 domain (residues 755-839), and a 25kDa fragment (residues 581-839). The soluble fusion proteins were captured with Ni2+ affinity chromatography, and subsequently cleaved with tobacco etch virus protease. Purification protocols yielded ∼10-15mg of pure protein from 1L of culture. Proper folding of the shorter domains was confirmed by heteronuclear NMR spectra recorded on 15N-labeled samples. A modified protocol for the native purification of the secreted 81kDa pro-protein of PrtV is provided. Proteolytic activity measurements suggest that the 37kDa catalytic metalloprotease domain alone is sufficient for activity.
Gesehen am 28.08.2020